Assessment of energy consumption as a performance index in high-rise buildings in Hanoi, Vietnam - Giang, N.D.; Ichinose, M.; Sasaki, R.; Tokuda, E. (Penerbit Universiti Kebangsaan Malaysia, 2017)
This research aims to at investigating the actual performance of high-rise office buildings in terms of the indoor environment and energy consumption. Data collection was based on the onsite measurement of five buildings in operation in Hanoi, Vietnam. The thermal environment, illuminance, CO2 concentration, and energy consumption were the basic parameters analyzed as a fundamental step toward realizing and determining energy-efficient buildings. The current situation can be roughly was described; the most of methodology follow the western standard and there still be less data that show the actual situation under building operation documented. To analyze and evaluate, this research conducted measurement of indoor environment quality (IEQ) and energy consumption of high-rise office buildings between 2014 and 2015 in Hanoi. From the result, it is presented evident that the overall energy consumption and indoor environment of office buildings in Vietnam are not in a negative situation to compare favorably with international standards. However, it is also presented that there is a large high fluctuation in the thermal environment. The electricity consumption has strong relationship with outdoor temperature obviously and the peak consumption is observed in the summer. The consumption doesn’t increase in winter despite indoor temperature show being lower than the standard comfort criteria-zone. This results in the lower energy consumption in the observed buildings due to the unique climate of Hanoi and inappropriate building operation mainly because of such as the insufficient operation of air conditioning systems and the air-tightness of building envelopes.